2009
DOI: 10.4067/s0717-75262009000400004
|View full text |Cite
|
Sign up to set email alerts
|

Sobrevida De Neonatos De Extremo Bajo Peso Al Nacer en Una Región Del Sur De Chile

Abstract: Caracterizar la sobrevida y factores asociados en prematuros de extremo bajo peso al nacer (EBPN). Método: Cohorte de 93 neonatos <1000g ingresados entre 2000-2005 a cuidado intensivo neonatal del Hospital Clínico Regional de Valdivia, Chile, seguidos hasta su egreso. Se calculó la sobrevida mediante método de Kaplan-Meier, evaluándose su relación con el peso al nacer (PN), edad gestacional (EG), adecuación PN-EG, Apgar, administración de corticoides prenatales (CPN) y surfactante, comparando curvas de sobrevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
2
0
2
Order By: Relevance
“…Some of the factors associated with neonatal death according to other studies in the literature did not appear in the final model of multivariate analysis in our study. Gestational age, for example, classically and inversely associated with greater risk of neonatal death (7,17,24) , did not remain significantly associated after data were analyzed together. Gestational age is not a precise measure and may be affected by the method used to define it: ultrasound, chronological criterion according to date of last menstruation, or clinical and neurological evaluation of the infant at birth.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Some of the factors associated with neonatal death according to other studies in the literature did not appear in the final model of multivariate analysis in our study. Gestational age, for example, classically and inversely associated with greater risk of neonatal death (7,17,24) , did not remain significantly associated after data were analyzed together. Gestational age is not a precise measure and may be affected by the method used to define it: ultrasound, chronological criterion according to date of last menstruation, or clinical and neurological evaluation of the infant at birth.…”
Section: Discussionmentioning
confidence: 83%
“…The use of antenatal corticosteroids has been shown to be an important protective factor for premature infants (25) . However, some authors did not find any differences in the survival of VLBW neonates when these drugs were used (24) . A study conducted in towns other than the capital city in the state of São Paulo found a reduction in the mortality of VLBW infants from 1995 to 2000.…”
Section: Discussionmentioning
confidence: 99%
“…6.1 "Los Estados Parte reconocen que todo niño tiene el derecho intrínseco a la vida"; art 6.2 "Los Estados Parte garantizarán en la máxima medida posible la supervivencia y el desarrollo del niño". Sin embargo, en muchas ocasiones las decisiones deben ser analizadas bajo el manto de un pronóstico incierto, que genera interrogantes de la calidad de vida en quienes cuidan a estos pacientes, y temores e inseguridades en los padres por situaciones difíciles de afrontar (Mendoza, Santander, Páez, & Barría, 2009). En los Estados Unidos, más de seis millones de parejas son estériles -definido como el estado después de un año de haber tratado de concebir sin conseguirlo, periodo que para las mujeres de mas de 35 años disminuye a seis meses-.…”
Section: Desarrollounclassified
“…El progreso de la neonatología ha sido efectivo, eficiente y eficaz de forma espectacular para reducir la mortalidad y morbilidad de los niños mayores de 1.000 g de peso al nacer, pero la muerte en el ámbito de los prematuros extremos continúa siendo frecuente, con una morbilidad que no se ha modificado (Stenson, 2017). Los RN con edad gestacional menor o igual a 32 semanas, tienen 3 veces más riesgo de morir si tienen un peso bajo los 1.000 g, con un peso bajo 600 g se estima 2,2 veces más riesgo de morir respecto de RN con un peso entre 900 y 999 g (Mendoza, Santander, Páez, & Barría, 2009).…”
Section: Introductionunclassified